Human security in Southeast Asia : 20 Years in review - Pitsuwan, Surin (2020)
The concept of human security gained prominence in Southeast Asia in the aftermath of the Asian financial crisis of 1997-1998. In a rapidly changing ASEAN, the list of human insecurities covers issues of both development and security, and fall within the ambit of both freedom from want and freedom from fear. But while human security has gained traction 20 years since the 1994 UNDP Human Development Report, more needs to be done to translate discourse into action. This article argues that in order to advance human security ASEAN states must be imbued with the political will to act decisively in addressing human insecurities and to work with other actors in promoting protection and empowerment of people and communities.